The popularity of winter sports in Russia according to television broadcasts of the 2018 and 2022 Olympic winter games - Shvetsov A.V.; Dimitrov I.L.; Polyanskaya I.S. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identify the most popular winter sports in Russia based on television broadcasts of the 2018 and 2022 Olympic Winter Games. on public Russian state television channels. Methods and structure of the study. The study included an analysis and synthesis of data from specialized and scientific-methodological literature, as well as a comparison of the main indicators of sports television broadcasts. Results and conclusions. Largely thanks to the interaction of the International Olympic Committee (IOC) with television, the Olympic Games (OG) have become the main sporting event in the world and a global phenomenon, and television has become one of the key partners of sports, providing its financing by purchasing rights to television broadcasts and displaying television advertising of sponsors, providing financial support to sports. Athletes of the USSR, and then Russia, won more than 80% of all medals won at the Olympic Winter Games (OSG) in competitions in cross-country skiing, speed skating, figure skating, biathlon and hockey. It has been established that it is competitions in these sports that have the highest ratings and arouse increased interest among television viewers on state Russian television channels when broadcasting the 2018 and 2022 Olympic Winter Games.